2004
DOI: 10.1115/1.1924433
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility Study of an On-Board Natural Gas to Dimethyl Ether Reactor for Dimethyl Ether Preinjection and Enhanced Ignition

Abstract: Dual fuel (CI) engines provide an excellent means of maintaining high thermal efficiency and power while reducing emissions. This is particularly true in situations where the main CI fuel does not exhibit good autoignition characteristics, such as diesel engines operating on natural gas usually in stationary applications such as a pipeline installation. This paper explores the feasibility of chemically synthesizing DME from natural gas “on-board” and using it as an ignition source for a dual fuel engine. Conve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Previous studies on GTL processes typically focus on process designs where the topology (i.e., the combination of process units and streams) is fixed. A process simulation is then conducted to determine the heat and mass balances for the process, and an economic analysis is performed to determine the viability of the plant . Although a process design can be developed in this fashion, this strategy will require a significant amount of computational time and manpower to find the “best possible” design that optimizes some predetermined objective (e.g., maximum profit and minimum cost).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies on GTL processes typically focus on process designs where the topology (i.e., the combination of process units and streams) is fixed. A process simulation is then conducted to determine the heat and mass balances for the process, and an economic analysis is performed to determine the viability of the plant . Although a process design can be developed in this fashion, this strategy will require a significant amount of computational time and manpower to find the “best possible” design that optimizes some predetermined objective (e.g., maximum profit and minimum cost).…”
Section: Introductionmentioning
confidence: 99%
“…The design and topology of the GTL refineries that may exist in the supply chain are optimized using the process synthesis methods developed by Baliban et al For GTL systems, typical studies have focused on fixed process designs and topologies where simulations have been used to determine the heat and mass balances for the process. ,,,,,− However, recent developments in process synthesis strategies for hybrid feedstock systems ,,,, ,,,, have shown that rigorous and computationally efficient methodologies can be developed and used to simultaneously analyze thousands of process designs to extract the optimal process design(s) and establish trade-offs among them. The superstructure optimization method can directly compare the technoeconomic and environmental benefits of GTL processes in a single mathematical model, simultaneously analyzing several existing or novel processes to determine the optimal topology, which will have either the lowest cost or the highest net present value.…”
Section: Gtl Refineriesmentioning
confidence: 99%
“…In this approach, DME is produced in three different isothermal reactors by the following steps: steam reforming, methanol synthesis, and DME synthesis . In the steam reforming step, natural gas is reacted with steam with nickel or magnesium oxide acting as catalysts to produce synthesis gas as shown in Eq.…”
Section: Case Study: Dimethyl Ether Production Processmentioning
confidence: 99%